Developing Knowledge and Leadership in Pre-Service Teacher Education Systems. (13th April 2015) - Ferreira, Jo-Anne; Ryan, Lisa; Davis, Julie
Abstract: Pre-service teacher education institutions are large and complex organisations that are notoriously difficult to change. One factor is that many change efforts focus largely on individual pre-service teacher educators altering their practice. We report here on our experience using a model for effecting change, which views pre-service teacher education institutions and educators as a part of a much broader system. We identified numerous possibilities for, and constraints on, embedding change, but focus only on two in this article: participants' knowledge of change strategies and their leadership capacities. As a result of our study findings and researcher reflections, we argue that being a leader in an academic area within pre-service teacher education does not equate to leadership knowledge or skills to initiate and enact systems-wide change. Furthermore, such leadership capacities must be explicitly developed if education for sustainability is to become embedded in pre-service teacher education.